2017
DOI: 10.3389/fphys.2017.00391
|View full text |Cite
|
Sign up to set email alerts
|

Irinotecan-Induced Gastrointestinal Dysfunction Is Associated with Enteric Neuropathy, but Increased Numbers of Cholinergic Myenteric Neurons

Abstract: Gastrointestinal dysfunction is a common side-effect of chemotherapy leading to dose reductions and treatment delays. These side-effects may persist up to 10 years post-treatment. A topoisomerase I inhibitor, irinotecan (IRI), commonly used for the treatment of colorectal cancer, is associated with severe acute and delayed-onset diarrhea. The long-term effects of IRI may be due to damage to enteric neurons innervating the gastrointestinal tract and controlling its functions. Balb/c mice received intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…These selected sections of colon were analyzed and scored the following parameters: changes in crypt architecture (0–5), reduction in crypt length (0–5), mucosal ulceration (0–5), and immune cell infiltration (0–5; total score 20). (McQuade et al, ) The morphological assessment was performed under a light microscope at a magnification of 100, which was connected to a computer with an image analysis program (Nikon NIS‐Elements).…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…These selected sections of colon were analyzed and scored the following parameters: changes in crypt architecture (0–5), reduction in crypt length (0–5), mucosal ulceration (0–5), and immune cell infiltration (0–5; total score 20). (McQuade et al, ) The morphological assessment was performed under a light microscope at a magnification of 100, which was connected to a computer with an image analysis program (Nikon NIS‐Elements).…”
Section: Methodsmentioning
confidence: 82%
“…Fecal parameters were analyzed according to earlier studies (McQuade et al, ; Zhou et al, ). Briefly, individual mice were placed in clean cages and allowed ad libitum access to food and water for 15–40 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that the delay in the gastric emptying was clearly observed as an increase in MAT value in the irinotecan-treated rats in the APAP study, but not in the DAB study. McQuade et al (2017) have previously reported that the gastric emptying rate was decreased by irinotecan treatment. Taken together, these findings suggest that the decrease in the plasma concentration of DAB is primarily explained by the increased P-gp function but not by the decrease in passive diffusion or gastric emptying.…”
Section: Discussionmentioning
confidence: 97%
“…For example, fecal pellets from mice repeatedly treated with the antineoplastic drug irinotecan showed statistically significant differences in length along treatment. 45 Likewise, vincristine, another antitumoral drug, reduced the diameter of fecal pellets in the rat, when repeatedly administered. 16 Whatever the case may be, the fact that morphometric values of the endogenous fecal pellets were not significantly changed in our experimental conditions imply that changes in fecal pellet propulsion did not involve altered mechanical stimulation of the colon associated to changes in fecal pellet size.…”
Section: Discussionmentioning
confidence: 99%